شعرية الموتنص وصف جو تاهرت في الشتاء لـ بكر بن حماد التاهرتي أنموذجًا - دغمان, علي (University of Eloued جامعة الوادي, 2018)
تسعى القراءة الحالية إلى مقاربة شعرية الموت؛ وهي ملصقة مفارقة إذ تتعيّن بمثابة الخامة التي تتّسع لمعاني ودلالات “شعر الزهد“، فيما تُخفي وجهًا آخر يتعيّن بمثابة القناع الذي يُوقع القارئ/ الضحية في خديعة المعنى الجاهز، أي “وصف جو تاهرت“ تحديدًا، بينما يُضمر معناه الخفيّ في طياته؛ وهو “مرثية تاهرت The present reading seeks to approach the poetry of death; it is a paradox etiquette, as it must be the material that expands on the meanings and signs of "ascetic poetry", while concealing another face that should serve as the mask that imposes the reader / victim in the deception of the ready meaning: "description weather of Tahert" specifically, Which is hidden in it; it is "the elegy of Tahert.
Keywords: شعر الزهد، وصف جو تاهرت، مرثية تاهرت; ascetic poetry, description weather of Tahert, the elegy of Tahert